A numerical and experimental study of distribution of the residual stress on the shot peened low alloy steel - Trung, Pham Quang (2019)
Shot peening is a cold working process, which is used to enhance the properties of materials, especially the fatigue life as it induces large compressive residual stresses in the subsurface of materials. In this paper, the effect of the shot peening process on the topography of the shot peened surface and the distribution of the residual stresses in the subsurface of the material was systematically investigated. A technique to estimate the shot peening coverage was employed using a finite element model which was further developed using experimental results for increased accuracy. The comparison between the numerical and experimental studies gives a good agreement of the distribution of the residual stresses in the subsurface of the shot peened material. The shot peening pressure and media size are two main factors affecting on the presence of compressive residual stresses in the subsurface of the material.